A Strange State of Mournful Contentment: The Role of Compassion in Moral Betterment - Candiotto, Laura (My University, 2023)
In this paper, I will consider a unique case in which changing one’s character is part of a process of moral betterment when facing oppression. By engaging with the Dutch-Jewish intellectual and Holocaust victim Etty Hillesum, I will highlight the situated dimension of moral betterment as a practice that is driven by the pressure of concurrent events. I will claim that moral betterment does not need to come out of an internal will to change for the better. Instead, I will argue that “bearing real suffering” (Hillesum 1996: 220) is what makes compassion a potential source of moral betterment. This is possible because, in compassion, one experiences emotional friction between weakness and strength in facing the suffering caused by oppression.
Podivný stav truchlivé spokojenosti: Úloha soucitu v morálním zlepšení
Keywords: moral betterment; compassion; Etty Hillesum; emotional friction; suffering; oppression; morální zlepšení; soucit; Etty Hillesum; citové třenice; utrpení; útlak